The effect of video training on pommel horse circles according to circle phase complexity - Baudry, L.; Leroy, D.; Seifert, L.; Chollet, D. (Journal of Human Movement Studies, 2005)
This study investigated whether the influence of video modeling on the circle performed on a pommel horse depends on the complexity of the circle's four phases. The video-modeling procedure, which was organised over four training days, associated expert-modeling with self-modeling and quantitative performance analysis. Sixteen gymnasts were assigned to one of two groups: a modeling group that received video-modeling feedback, or a control group that received no feedback. The results are presented in three parts (pre-test, acquisition and performance analysis). Pre-test analysis revealed that the body was more aligned for the back phase than for the front entry and exit phases for both groups. Acquisition analysis showed that the modeling group gymnasts improved their body segmental alignment during the back phase quicker than during the entry and exit phases. At the end of this acquisition phase, the gains were 7.3±3.3% (back phase), 5.4±1.9% (front phase), 2.6±0.8% (entry phase) and 1.9+1.6% (exit phase). Performance analysis at the end of the training sessions revealed that, as predicted, the more complex circle phases (entry and exit) were less enhanced than the other two phases (front and back). It thus appears that immediate video-modeling may help to correct complex sports movements such as the circle performed on the pommel horse. However, the effectiveness seems to be dependent on the complexity of the phase.